(untitled) (Texas Journal of Medical Science, 2023)
The article presents clinical and genetic features and prognostic criteria for juvenile idiopathic arthritis. The clinical features of the disease, the results of laboratory analysis are important when choosing an effective method of treatment. Depending on the severity of the disease, the characteristics of the clinical course and the results of the functional laboratory analysis, drug and surgical treatment of joints is recommended